2022
DOI: 10.3390/ani12081031
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Molecular Characterization of Cryptosporidium spp. in Dairy Cattle and Dairy Buffalo in Yunnan Province, Southwest China

Abstract: Cryptosporidium spp. are important foodborne and waterborne pathogens in humans and animals, causing diarrheal diseases. Cattle are one of the reservoirs of Cryptosporidium infection in humans. However, data on the occurrence of Cryptosporidium spp. in cattle in Yunnan Province remains limited. A total of 700 fecal samples were collected from Holstein cows (n = 442) and dairy buffaloes (n = 258) in six counties of Yunnan Province. The occurrence and genotypes of Cryptosporidium spp. were analyzed using nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…For dairy cattle, the Cryptosporidium spp. infection rate in the present study was higher than the corresponding rates previously reported for Ningxia Autonomous Region (1.6%, 23/1366) [ 31 ], Anhui Province (2.1%, 11/526) [ 32 ], Xinjiang Uyghur Autonomous Region (4.3%, 60/1391) [ 33 ], Shanxi Province (1.0%, 4/394) [ 7 ], Guangdong Province (4.4%, 63/1440) [ 34 ], and Gansu Province (5.1%, 58/1257) [ 35 ] but lower than those reported for Sichuan Province (14.4%, 40/278) [ 36 ], Yunnan Province (14.7%, 65/442) [ 37 ], Jiangxi Province (26.1%, 43/165) [ 38 ], Taiwan Province (26.5%, 60/226) [ 39 ], and Inner Mongolia (29.9%, 151/505) [ 40 ]. For beef cattle, the Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…For dairy cattle, the Cryptosporidium spp. infection rate in the present study was higher than the corresponding rates previously reported for Ningxia Autonomous Region (1.6%, 23/1366) [ 31 ], Anhui Province (2.1%, 11/526) [ 32 ], Xinjiang Uyghur Autonomous Region (4.3%, 60/1391) [ 33 ], Shanxi Province (1.0%, 4/394) [ 7 ], Guangdong Province (4.4%, 63/1440) [ 34 ], and Gansu Province (5.1%, 58/1257) [ 35 ] but lower than those reported for Sichuan Province (14.4%, 40/278) [ 36 ], Yunnan Province (14.7%, 65/442) [ 37 ], Jiangxi Province (26.1%, 43/165) [ 38 ], Taiwan Province (26.5%, 60/226) [ 39 ], and Inner Mongolia (29.9%, 151/505) [ 40 ]. For beef cattle, the Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be related to the fact that all fecal samples used in this study were from calves. Past studies have shown that this parasite affects calves and weaned calves more than adults [ 26 , 29 , 30 ]. The correlation between age and Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies showed that younger animals were more susceptible to Cryptosporidium spp. due to their compromised immune system [ 18 , 28 , 44 , 56 ]. In the farms sampled in this study, calves were separately fed in enclosures with more suitable temperature and humidity, which may be one of the reasons for the low prevalence of Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%